The Cultural and Muamalah Perspective on the Practices of Paroan Cooperation Agreements among Rice Farmers - Mongkito, Abdul Wahid; Putra, Trisno Wardy; Rahayu, Siti; Hasanah, Nurul (KARSA Journal of Social and Islamic Culture, 2024)
This research aims to explain how the practice of paroan cooperation is implemented among rice farmers in Cialam Jaya Village, Konda District, how it is adapted from the perspective of cultural and Islamic traditions, and how it is adapted to the muzara'ah contract. This type of qualitative research uses several techniques, namely observation and interviews. The data analysis method used is data reduction; the results of the research show that in Cialam Jaya Village, Konda District, many people carry out cooperation agreements or what they call Paroan cooperation agreements, which are almost similar to the Muzara'ah agreement in Islam to carry out profit sharing cooperation in rice farming, but this does not mean that the people of Cialam Jaya village, Konda District, carry out the Paroan cooperation agreement in a haphazard manner but rather with the principles of transactions contained in Islam. The majority of Muslim communities make Paroan and muzara'ah cooperation contracts commensurate with fulfilling three elements in implementing the muzara'ah contract: (1) the existence of a contract or agreement between the land owner and the cultivator, (2) there is a profit-sharing system with a specific ratio, (3) the land owner provides all needs (seeds, fertilizer).